To investigate the correlation between the visual prostate symptom score, the international prostate symptom score, and uroflowmetry parameters in adult Thai males of different educational levels - Vasun Setthawong (2018)
© 2018 Background: To evaluate the correlation between the International Prostate Symptom Score (IPSS), Visual Prostate Symptom Score (VPSS), and uroflowmetry parameters in Thai males and to examine the possibility in establishing a severity cut-off point for VPSS. Methods: Between 1stFebruary and 31stMay 2016 a total of 200 men were enrolled onto the study and divided into high and low educated groups. All of them were requested to complete paperwork including their personal data, and then to complete a VPSS and IPSS questionnaire. Uroflowmetry, residual urine and prostate size were measured. The relationship between the answers to the VPSS and IPSS together with the other objective parameters was assessed using Spearman's rank test. Results: The mean age of the patients was 61.2 years. 69.9% of subjects were highly educated. There was a statistically significant correlation between VPSS and IPSS in total, and any individual scores except frequency score. There was weak correlation between the VPSS and the uroflowmetry parameters and prostate size. The low educated group had a statistically significant lower completion rate of both the VPSS (41.6% vs. 79.8%) and IPSS (61.2% vs. 81.2%) without assistance than the higher educated group and most of the lower educated group felt that the IPSS was easier to understand than the VPSS (51.2% vs. 48.8%, P < 0.001). A VPSS severity score ≤6 or ≥14 had a very high specificity that predicted the patients would have mild or severe symptoms (94.7% and 98.6%) while a VPSS between 7 and 13 had a high sensitivity (90.8%) but a low specificity (16.9%) when it came to the prediction of moderate symptoms. Conclusion: VPSS showed a significant correlation to the IPSS and uroflowmetry parameters. A VPSS score ≤6, 7 to 13 and ≥14 may indicate mild, moderate, and severe symptoms respectively.